K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

c: 2|x-3|=500

=>|x-3|=250

=>x-3=250 hoặc x-3=-250

=>x=253 hoặc x=-247

d: x-17=-8+(-17)

=>x-17=-25

hay x=-8

 

c: 2|x-3|=500

=>|x-3|=250

=>x-3=250 hoặc x-3=-250

=>x=253 hoặc x=-247

d: x-17=-8+(-17)

=>x-17=-25

hay x=-8

 

 

c: 2|x-3|=500

=>|x-3|=250

=>x-3=250 hoặc x-3=-250

=>x=253 hoặc x=-247

d: x-17=-8+(-17)

=>x-17=-25

hay x=-8

 

 

c: 2|x-3|=500

=>|x-3|=250

=>x-3=250 hoặc x-3=-250

=>x=253 hoặc x=-247

d: x-17=-8+(-17)

=>x-17=-25

hay x=-8

 

 

c: 2|x-3|=500

=>|x-3|=250

=>x-3=250 hoặc x-3=-250

=>x=253 hoặc x=-247

d: x-17=-8+(-17)

=>x-17=-25

hay x=-8

 

 

c: 2|x-3|=500

=>|x-3|=250

=>x-3=250 hoặc x-3=-250

=>x=253 hoặc x=-247

d: x-17=-8+(-17)

=>x-17=-25

hay x=-8

7 tháng 4 2016

a)10

b)-16

c)20 hoặc -17

d)-3 hoặc 3

7 tháng 4 2016

a) 3x-17=x+3

=>3x-x =3+17

=>2x     =20

=>x       =20:2

=>x       =10

b) 2x-15=-47

=>2x     =-47+15

=>2x     =-32

=>x       =-32:2

=>x       =-16

c) Ix-3I-12=I-5I

=>Ix-3I-12=5

=>Ix-3I     =5+12

=>Ix-3I     =17

TH1 x-3=17

       x    =17+3

        x   =20

TH2 x-3=-17

       x   =-17+3

       x    =-14

Vậy x=-14;20

d) (x-3)x(2x+6)=0

Để biểu thức trên bằng 0

<=> x-3=0=>x=0+3=>x=3

       x=0

       2x+6=0=>2x=0-6=>2x=-6=>x=-6:2=>x=-3

Vậy x=-3;0;3

29 tháng 12 2017

a, =>5+x -(-16) = -20

=> 5+x+16 = -20

=> x+21 = -20

=> x = -20 - 21 = -41

c, => 27-|x-5| = 12+3 = 15

=> |x-5| = 27 - 15 = 12

=> x-5=12 hoặc x-5=-12

=> x=17 hoặc x=-7

k mk nha

29 tháng 12 2017

cám ơn bạn